Seni Menyusun Judul Penelitian: Menyederhanakan Ide, Memaksimalkan Makna - Saputra, Sahdan; Hendri, Wira; Ihyani, Layali (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
This community engagement program, titled "The Art of Composing Research Titles: Simplifying Ideas, Maximizing Meaning," was designed to enhance the ability of students in the Management Program at Bumigora University to formulate effective, relevant, and academically appealing research titles. Employing the Participatory Action Research (PAR) approach, the program involved 20 students and consisted of preparatory surveys, theoretical sessions, and hands-on training. Key topics included the characteristics of strong research titles, title formulation techniques for qualitative and quantitative methods, and practical revision of participants' initial drafts. Post-training evaluations indicated significant improvements, with 90% of participants successfully revising their titles to be more focused and concise. Additionally, 88% reported increased confidence in presenting their research ideas. The program's outcomes demonstrate its effectiveness in addressing students' challenges in title formulation while fostering critical and creative thinking. This initiative emphasizes the importance of structured and interactive learning processes in academic skill development.